Internal Training untuk Meningkatkan Komunikasi Interpersonal Karyawan - Liset Ayuni; Isthi Angela Apriliani; Ima Fitri Sholichah (Medan Resource Center, 2022)
In the 5.0 era, business competition has become increasingly dynamic. This has spurred company managers to think more complexly so that companies can survive, even making them superior to competitors. Therefore, this study aims to empirically test the results of providing internal training to employees at PT.X to improve interpersonal communication. The population in this study were employees at PT.X which involved 14 employees to be used as samples taken using saturated sampling techniques and questionnaires. The scale used for data collection is the interpersonal communication scale by Devito (2011). The results of the different tests show that there is a significant difference between the pre-test and post-test values ??of employees to improve interpersonal communication, namely the Z value obtained is -2.844 with a p value (Asymp. Sig 2 tailed) of 0.004 which is less than the critical research limit of 0.05 (0.004 <0.05) so the decision hypothesis is to accept H1 or which means there is an increase in interpersonal communication after internal training.